2019
DOI: 10.1002/ajoc.201800710
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed C(sp2)−H Activation for the Formation of C−N Bonds: Rapid Access to Benzimidazoquinazolines

Abstract: A convenient and effective method for Pdcatalyzed cross-dehydrogenative C(sp 2 )À H/NÀ H couplings to synthesize fused N-heterocyclic benzimidazoquinazoline derivatives was developed. The reaction employs Pd(OAc) 2 as the catalyst and Cu(OAc) 2 or O 2 (from the air) as the terminal oxidant. The strategy uses simple and easily accessible substrates. This method provides a route to azole-fused heterocycles.[a] X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…12,13‐Dimethylbenzo[4,5]imidazo[1,2‐ a ]benzo[4,5]imidazo[1,2‐ c ]quinazoline (3 f) [9] . Purified by TLC (dichloromethane/MeOH=99/1, 2 times); white solid (66 mg, 65 %); mp 315–317 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13‐Dimethylbenzo[4,5]imidazo[1,2‐ a ]benzo[4,5]imidazo[1,2‐ c ]quinazoline (3 f) [9] . Purified by TLC (dichloromethane/MeOH=99/1, 2 times); white solid (66 mg, 65 %); mp 315–317 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Scaffold A can also be synthesized by stepwise C(sp 2 )−N coupling and oxidative cycliztion of 2‐(2‐bromophenyl)benzimidazole with benzimidazole as a building block in the presence of CuI/Pd(OAc) 2 /Cu(OAc) 2 or CuCl 2 /1,10‐phenanthroline (Scheme 1, route b) [7,8] . Such a similar construction of scaffold A using benzimidazole as a building block was also exemplified by Pd‐catalyzed C(sp 2 )−N coupling and cross‐dehydrogenative C(sp 2 )−H/N−H coupling between 2‐phenylbenzimidazole and benzimidazole (Scheme 1, route c) [9] . During the course of our recent efforts directed toward copper‐catalyzed and transition metal‐free synthesis of polynuclear N‐fused hybrid scaffolds via a C(sp 2 )−N coupling, we also recently reported that 2‐(2‐bromophenyl)benzimidazoles were coupled and cyclized with cyclic ureas as building blocks in the presence of CuI to produce scaffold A (Scheme 1, route d) [10,11] .…”
Section: Introductionmentioning
confidence: 97%
“…DeBoef et al employed Pd(II)/Cu(I) catalysis with the oxidant of Cu(OAc) 2 to effect oxidative dehydrogenative coupling of 1-benzyl substituted benzimidazoles ( Scheme 30 a) [ 94 ]. The Pd(II) C-H aryl-activation of 2-phenylbenzimidazoles with C-N coupling of two benzimidazole fragments gave benzimidazoquinazolines, with Cu(OAc) 2 or air being the terminal oxidants ( Scheme 30 b) [ 95 ].…”
Section: Syntheses Of Ring-fused Benzimidazoles and Imidazobenzimidazolesmentioning
confidence: 99%
“…More recently, 2-(2-bromoaryl)- and 2-(2-bromovinyl)benzimidazole substrates were coupled with cyanamide using CuI to give 2-aminoquinazoline and 2-aminopyrimidine hybrid structures ( Scheme 31 b) [ 97 ]. Similar conditions allowed CuI-mediated coupling and cyclization between 2-(2-bromoaryl)indoles and 2-aminoazoles [ 98 ], including 2-aminobenzimidazoles with loss of ammonia to give indole analogues of Scheme 30 b adducts [ 95 ].…”
Section: Syntheses Of Ring-fused Benzimidazoles and Imidazobenzimidazolesmentioning
confidence: 99%
See 1 more Smart Citation